2017
DOI: 10.1097/scs.0000000000002615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Low-Dose Alendronate Injections Into the Distraction Gap on New Bone Formation and Distraction Rate on Distraction Osteogenesis

Abstract: Bisphosphonates that constrain bone resorption have a direct effect on osteoclast function. In this experimental study, the effects of low-dose local alendronate injections on the distraction gap (DG) in rabbit mandible at 2 different rates were evaluated.The experimental study was conducted on 20 male, New Zealand white rabbits. The animals were divided into 3 experimental groups and 1 control group. Group 1 consisted of animals with distraction at the rate of 1 mm/day, receiving postoperative local low-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In Alp et al’ utilized a rate of 1 mm/day lengthening and locally injected low-dose alendronate in rabbit mandibles, which provided the optimal new bone formation. This suggested that bisphosphonates might be beneficial in clinical practice ( Alp et al, 2017 ).…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…In Alp et al’ utilized a rate of 1 mm/day lengthening and locally injected low-dose alendronate in rabbit mandibles, which provided the optimal new bone formation. This suggested that bisphosphonates might be beneficial in clinical practice ( Alp et al, 2017 ).…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…In the literature, there have been studies on bone regeneration that used many different materials, techniques (low-intensity pulsed ultrasound, pulsed electromagnetic fields, dynamic loading, etc. ), and pharmacological agents to increase the treatment success rate by improving the quality and resistance of the regenerative tissue [6][7][8][9][10][11][12][13]. On the other hand, gene therapy in rabbits needs to be investigated further to validate the results and test them clinically [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides their inhibitory effect on osteoclasts and bone resorption, bisphosphonates may promote the processes of bone formation and enhance osteogenic differentiation of mesenchymal stem cells (MSCs) [17]. Bisphosphonates have been shown to support osseous wound healing and bone formation in the animal model [18,19]. Dental implant bisphosphonate coatings are successfully applied as local drug delivery systems, demonstrating higher bone to implant contact (BIC) and peri-implant bone mineralization in the animal model [20,21].…”
Section: Introductionmentioning
confidence: 99%